Revealing emerging science and technology research for dentistry applications of 3D bioprinting - Rodriguez-Salvador, Marisela (Int J Bioprint, 2018)
Science and technology (S&T) on three-dimensional (3D) bioprinting is growing at an increasingly accelerated pace; one major challenge represents how to develop new solutions for frequent oral diseases such as periodontal problems and loss of alveolar bone. 3D bioprinting is expected to revolutionize the health industry in the upcoming years. In dentistry, this technology can become a significant contributor. This study applies a Competitive Technology Intelligence methodology to uncover the main S&T drivers in this domain. Looking at a 6-year period from 2012 to 2018 an analysis of scientific and technology production was made. Three principal S& T drivers were identified: Scaffolds development, analysis of natural and synthetic materials, and the study of scaffold characteristics. Innovative hybrid and multiphasic scaffolds are being developed to regenerate periodontal tissue and alveolar bone by combining them with stem cells from the pulp or periodontal ligament. To improve scaffolds performance, biodegradable synthetic polymers are often used in combination with bioceramics. The characteristics of scaffolds such as fiber orientation, porosity, and geometry, were also investigated. This research contributes to people interested in bringing innovative solutions to the health industry, particularly by applying state-of-the-art technologies such as 3D bioprinting, in this case for dental tissues and dental bone diseases.